Peran Pendidikan Kewarganegaraan dalam Membentuk AI Literacy dan Etika Digital Mahasiswa di Era Artificial Intelligence: The Role of Citizenship Education in Forming AI Literacy and Digital Ethics of Students in the Era of Artificial Intelligence - Ahmad Muhamaad Mustain Nasoha; Giral Ilham Bagus Pramudiansyah; Abi Pradana; Fajar Imam Syafei; Muhamad Nafiuidin Al Hasani (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The rapid development of Artificial Intelligence (AI) has presented ethical challenges and new digital literacy for the world of higher education. Students as a native digital generation need to be equipped with AI literacy capabilities and strong understanding of digital ethics in order to be able to adapt critically and responsibly in artificial intelligence-based digital ecosystems. This study aims to analyze the role of citizenship education (PKN) in forming AI Literacy and digital ethics of students in the AI era. The research method used is a descriptive-qualitative approach with data collection techniques through literature studies, class observations, and interviews with lecturers and students in three state universities. The results showed that PKN had a significant contribution in instilling ethical awareness, social responsibility, and critical thinking of the use of AI technology. Integration of material about digital rights, data privacy, and moral responsibility in the PKN curriculum are proven to increase student understanding of the social impact and AI ethics. In conclusion, citizenship education plays a strategic role as a vehicle for the formation of intelligent, ethical, and integrity of digital citizens in facing social transformation due to the development of AI. The recommendation of this study emphasized the importance of adaptive PKN curriculum renewal of the dynamics of technology and strengthening digital ethical literacy in the higher education environment. (Keywords: Citizenship Education, AI Literacy, Digital Ethics, Students, Artificial Intelligence